2011
DOI: 10.1007/s11142-011-9166-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-GAAP earnings and board independence

Abstract: We examine the association between board independence and the characteristics of non-GAAP earnings. Our results suggest that companies with less independent boards are more likely to opportunistically exclude recurring items from non-GAAP earnings. Specifically, we find that exclusions from non-GAAP earnings have a greater association with future GAAP earnings and operating earnings when boards contain proportionally fewer independent directors. Consistent with the association between board independence and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(101 citation statements)
references
References 71 publications
(122 reference statements)
4
94
2
1
Order By: Relevance
“…This is done via controlling and monitoring the corporate managers' opportunistic behavior. Consequently, Frankel, McVay and Soliman (2011), independent directors on the board may significantly contribute in the monitoring of the construction of financial reports by the management.…”
Section: Board Independencementioning
confidence: 99%
“…This is done via controlling and monitoring the corporate managers' opportunistic behavior. Consequently, Frankel, McVay and Soliman (2011), independent directors on the board may significantly contribute in the monitoring of the construction of financial reports by the management.…”
Section: Board Independencementioning
confidence: 99%
“…Control variables, to control for potential correlated omitted variables, are identified based on previous studies (Kolev et al, 2008;Frankel et al, 2011;and Kyung 2014): Growth, Ln(Size), Loss, Earnings_Volatility, and Book_to_Market_Assets, each of which is anticipated to be correlated with both Non_GAAP_Earnings and Future-Operating_Earnings. 12 The analysis further includes the natural logarithm of Ln(Size) to deal with skewness in the distribution of the dependant variables.…”
Section: Empirical Testsmentioning
confidence: 99%
“…12 The analysis further includes the natural logarithm of Ln(Size) to deal with skewness in the distribution of the dependant variables. To further control for size effects in the analysis (following Kolev et al, 2008 andFrankel et al, 2011), variables such as SUM_FutOpEarn, GAAP_Earnings, Non_GAAP_Earnings, Total_Exclusions, Special_Items, Other_Exclusions, and Growth are standardised by total assets per share. All continuous variables are further winsorized at the top and bottom two percent to avoid undue influence by outliers.…”
Section: Empirical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in the area of earnings management has identified asymmetries in the frequency distribution of the earnings metric near specific earnings target thresholds (essentially following seminal works by Hayn, and Burgstahler and Dichev, ). The most common thresholds employed are (i) zero (e.g., Burgstahler and Dichev, ; Degeorge et al., ; Bhattacharya et al., ; Burgstahler and Eames, ; Lang et al., ; Barua et al., ; and Dierynck et al., ), (ii) previous‐period value (e.g., Burgstahler and Dichev, ; Degeorge et al., ; Beatty et al., ; Barua et al., ; and Frankel et al., ), and (iii) analysts’ consensus forecasts (e.g., Degeorge et al., ; Brown and Higgins, , ; Burgstahler and Eames, ; Koh et al., ; Barua et al., ; and Eames and Kim, ).…”
Section: Related Literaturementioning
confidence: 99%